Cellulose Isolated From Waste Rubber Wood and Its Application in PLA Based Composite Films - Ou, Zhiqiang; Zhou, Qi; Rao, Xin; Yang, Haifeng; Huo, Chunqing; Du, Xueyu (Frontiers in Bioengineering and Biotechnology, 2021)
Waste rubber wood is the castoff of rubber plantation with abundant reservation but without high-value utilization. In this study, cellulose with high purity has been efficiently isolated from waste rubber wood and further processed into cellulose nanocrystals. By means of acetylation, more hydrophobic cellulose-based products, namely acetylated rubber wood cellulose (Ac–RWC) and acetylated rubber wood cellulose nanocrystals (Ac–RW–CNC) had been attempted as reinforcing fillers for fabricating two series of PLA-based composite films via spin coating instead of currently prevailing melt compounding technique. To ensure a uniformed dispersion of fillers in PLA matrix, the addition of reinforcing filler should be equal to or less than 5% based on the film dry weight. Compared with pure PLA film, the Ac–RWC reinforced PLA composite films are more thermally stable, while the Ac–RW–CNC reinforced PLA composite films on the other hand exhibit more enhanced performance in mechanical properties and the degree of crystallinity.